Polyclonal antibodies for the detection of Trypanosoma cruzi circulating antigens. - Edith S Málaga-Machaca; Alessandra Romero-Ramirez; Robert H Gilman; Sofía Astupiña-Figueroa; Noelia Angulo; Alejandro Florentini; Cinthya J Lovon-Luque; Remo A Gonza; Ada Del Carpio-Sanz; Inés Cabello; Rosina Camargo; Fernando Recuenco; et al. (Public Library of Science (PLoS), 2017)
Detection of Trypanosoma cruzi antigens in clinical samples is considered an important diagnostic tool for Chagas disease. The production and use of polyclonal antibodies may contribute to an increase in the sensitivity of immunodiagnosis of Chagas disease.Polyclonal antibodies were raised in alpacas, rabbits, and hens immunized with trypomastigote excreted-secreted antigen, membrane proteins, trypomastigote lysate antigen and recombinant 1F8 to produce polyclonal antibodies. Western blot analysis was performed to determine specificity of the developed antibodies. An antigen capture ELISA of circulating antigens in serum, plasma and urine samples was developed using IgY polyclonal antibodies against T. cruzi membrane antigens (capture antibody) and IgG from alpaca raised against TESA. A total of 33 serum, 23 plasma and 9 urine samples were analyzed using the developed test. Among serum samples, compared to serology, the antigen capture ELISA tested positive in 55% of samples. All plasma samples from serology positive subjects were positive in the antigen capture ELISA. All urine positive samples had corresponding plasma samples that were also positive when tested by the antigen capture ELISA.Polyclonal antibodies are useful for detection of circulating antigens in both the plasma and urine of infected individuals. Detection of antigens is direct evidence of the presence of the parasite, and could be a better surrogate of current infection status.